2020
DOI: 10.1002/ange.202007907
|View full text |Cite
|
Sign up to set email alerts
|

Ladder‐Type Heteroheptacenes with Different Heterocycles for Nonfullerene Acceptors

Abstract: The design, synthesis,a nd characterization of two novel nonfullerene acceptors (M8 and M34) based on laddertype heteroheptacenes with different heterocycles are reported. Replacing the furan heterocycles with the thiophene heterocycles in the heteroheptacene backbone leads to ahypsochromically shifted absorption band and greatly improved carrier transport for the resulting nonfullerene acceptor (M34) although the p-p-stacking distances are barely affected. Bulk-heterojunction polymer solar cells fabricated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
(6 reference statements)
0
11
0
Order By: Relevance
“…[21,22] Therefore, it is needed to consider the utilization of Dcores without the sp 3 -hybridized carbon by which the resulting nonfullerene acceptors may have enhanced charge transport and therefore improved photovoltaic performance.R ecently,o ur group reported two A-D-A nonfullerene acceptors (M34 and M8 in Figure 1) using two different heteroheptacenes which are both free of the sp 3 -hybridized carbon. [23] We found that the replacement of furan heterocycles with thiophene heterocycles in the Du nit led to the nonfullerene acceptor (M34) with an outstanding PCE of 15.24 %i nc omparison with the furan-based counterpart (M8) which exhibited al ower PCE of 4.21 %. These results suggest the importance of the aromatic nature of heteroheptacene core on photovoltaic performance of the nonfullerene acceptors.Furthermore,we demonstrated that the end groups (A) on these heteroheptacene-based nonfullerene acceptors can also significantly affect their photovoltaic performance.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…[21,22] Therefore, it is needed to consider the utilization of Dcores without the sp 3 -hybridized carbon by which the resulting nonfullerene acceptors may have enhanced charge transport and therefore improved photovoltaic performance.R ecently,o ur group reported two A-D-A nonfullerene acceptors (M34 and M8 in Figure 1) using two different heteroheptacenes which are both free of the sp 3 -hybridized carbon. [23] We found that the replacement of furan heterocycles with thiophene heterocycles in the Du nit led to the nonfullerene acceptor (M34) with an outstanding PCE of 15.24 %i nc omparison with the furan-based counterpart (M8) which exhibited al ower PCE of 4.21 %. These results suggest the importance of the aromatic nature of heteroheptacene core on photovoltaic performance of the nonfullerene acceptors.Furthermore,we demonstrated that the end groups (A) on these heteroheptacene-based nonfullerene acceptors can also significantly affect their photovoltaic performance.…”
Section: Introductionmentioning
confidence: 91%
“…[25][26][27] Herein, we design and synthesize three novel nonfullerene acceptors (MQ3, MQ5, and MQ6 in Figure 1) based on different heterocycles-based heteroheptacenes that are all free of sp 3 -hybridized atoms.A sw eh ave demonstrated previously,t he two pairs of bulky branched neighboring side chains on the central core can restrict the immoderate intermolecular aggregation thereby benefiting suitable phase separation of the resulting acceptor materials with donor materials. [23,24] All the three acceptors have the same A-D-A type backbone with identical side-chains and the same end groups of 2-(5,6-difluoro-3-oxo-2,3-dihydro-1H-inden-1-ylidene)malononitrile (IC2F). However,t hey differ either in the number or the position of selenophene heterocycle in the central Dc ore.Due to the lower aromaticity of selenophene in comparison with thiophene,w er eplace one or two thiophene rings with selenophene rings for achieving nonfullerene acceptors with reduced band gaps (compared with M34).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The rapid development of non-fullerene acceptors (NFAs), [4][5][6] notably ITIC [7] and Y6 [8] have greatly advanced the power conversion efficiency (PCE) of OSCs to reach 19 % [9][10][11] with facilely tailored chemical structures and precisely tunable band gaps, energy levels, and crystallization properties. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] In addition to NFAs, donor materials also play a crucial role in improving the device efficiencies. [29][30][31] Compared to polymer donors (PDs), smallmolecule donors (SMDs) can provide better batch-to-batch reproducibility due to well-defined chemical structure of SMDs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Organic solar cells (OSCs) are promising cost-effective, light-weight alternatives to silicon-based solar cells for certain applications. [5][6][7][8][9][10][11][12][13][14][15][16] Plentiful active layer materials, such as PM6 17 , PM7 18 , PM6-Tz20 19 , PTQ10 20 , D18 21 , M34 22 , Y6 23 , BTP-4Cl 24 and their analogues, have been explored to boost the efficiency of OSCs to over 16%. 25 In contrast, it is more challenging to develop efficient interface materials with all requirements of high conductivity, proper work function/energy levels, and orthogonal solubility, etc., and very limited types of efficient organic semiconducting interfaces were employed for high-performance OSCs.…”
Section: Introductionmentioning
confidence: 99%